Do hip and groin muscle strength and symptoms change throughout a football season in professional male football players? A prospective cohort study with repeated measures - van Klij, P.; Langhout, R.; van Beijsterveldt, A. M. C.; Stubbe, J. H; Weir, A.; Agricola, R.; Fokker, Y.; Mosler, A. B.; Waarsing, J. H.; Verhaar, J.; Tak, I. (Journal of Science and Medicine in Sport, 2021)
Objectives: Groin injuries are common in professional male football and result in significant complaints, time-loss and cost. We aimed to study: 1. Normal values of hip muscle strength and self-reported hip and groin function (Hip And Groin Outcome Score (HAGOS)). 2. Changes in these values throughout the season. 3. If previous (groin) injuries, leg dominance or league were associated with these outcome measures. Design: Prospective cohort study. Methods: 313 professional male football players (11 clubs) participated. Player characteristics and previous injuries were registered. Hip muscle strength (hand-held dynamometer) and HAGOS measurements were done at the start, middle and end of the season. Results: Data from 217 players were analysed. Adduction strength (mean ± standard deviation, Nm/Kg) was 3.40 ± 0.72 (start), 3.30 ± 0.65 (mid) and 3.39 ± 0.74 (end) (p = 0.186). Abduction strength was 3.45 ± 0.67, 3.14 ± 0.57 and 3.28 ± 0.61 (p < 0.001). Adduction/abduction ratio was 1.00 ± 0.21, 1.07 ± 0.22 and 1.05 ± 0.23 (p < 0.001). Statistically, the HAGOS-subscale `Pain` (median [interquartile range]) deteriorated slightly during the season (p = 0.005), especially from mid-season (97.5 [90.6-100.0]) to end-of-season (95.0 [87.5-100.0]) (p = 0.003). Other subscale scores remained unchanged between time points; 85.7 (symptoms), 100.0 (daily living), 96.9 (sports and recreation) 100.0, (physical activities) and 90.0 (quality of life). Previous injuries were associated with lower HAGOS-scores. Dominant legs had higher abduction strength (p < 0.001) and lower adduction/abduction ratio (p < 0.001). No differences between leagues were found for hip muscle strength and HAGOS-scores. Conclusions: In Dutch male professional football players, hip muscle strength and HAGOS-scores remained relatively stable throughout the season. Pain increased slightly, which while statistically significant, was not clinically relevant.